Detection of markers predictive of macrolide and fluoroquinolone resistance in Mycoplasma genitalium from patients attending sexual health services in England. (17th July 2017) - Pitt, Rachel; Fifer, Helen; Woodford, Neil; Alexander, Sarah
Abstract : Objectives: Resistance to both macrolides and fluoroquinolones has been reported in Mycoplasma genitalium; however, due to limited diagnostics, studies are often small and confined to specific geographical areas. This study sought to determine the rate of predicted resistance in M. genitalium -positive specimens referred for diagnostic testing. Methods: Seventy-four M. genitalium -positive specimens, referred to the national reference laboratory (2010-2013) from 19 centres across England, were blinded and anonymised. Specimens were examined for markers predictive of resistance to macrolides and fluoroquinolones using PCR followed by sequence analysis of 23 S rRNA gene, or gyrA and parC, respectively. Results: 23 S rRNA gene PCR sequencing revealed that 82.4% (61/74) of specimens harboured a single nucleotide polymorphism (SNP) associated with macrolide resistance. Differences were observed between the rates of predicted macrolide resistance in male (95.1% (58/61)) and female (23.1% (3/13)) patients (P = <0.001). By contrast, all specimens for which sequencing data were available (73/74) yielded wild-type gyrA sequences; and 58/61 (95.1%) had wild-type parC genes. Three specimens (3/61 4.9%) had SNPs in the parC gene associated with fluoroquinolone treatment failure, and all three also had predicted resistance to macrolides. Conclusions: Eighty-two per cent and 4.9% of M. genitalium specimens had SNPs associated with macrolide and fluoroquinolone resistance, respectively. Due to lack of widespread availability of testing for M. genitalium in the UK, this study sample was likely to be sourced from patients who may have already failed first-line macrolide therapy. Nevertheless, this study highlights the need for both greater access to M. genitalium diagnostics and genetic antimicrobial resistance testing.